Substituting Sedentary Time With Physical Activity in Fibromyalgia and the Association With Quality of Life and Impact of the Disease: The al-Ándalus Project - Gavilán-Carrera, Blanca; Segura-Jiménez, Víctor; Mekary, Rania A; Borges-Cosic, Milkana; Acosta-Manzano, Pedro; Estévez-López, Fernando; Álvarez-Gallardo, Inmaculada C; Geenen, Rinie; Delgado-Fernández, Manuel (Wiley, 2019)
Objective: There is an overall awareness of the detrimental health effects of sedentary time (ST) in fibromyalgia; however, data are limited on how replacement of ST with physical activity (PA) of different intensity may be related to health in this condition. The aim of this study was to examine how a substitution of ST with light PA (LPA) or moderate-to-vigorous PA (MVPA) is associated with quality of life and disease impact. Methods: This study comprised 407 women with fibromyalgia, mean ± SD age 51.4 ± 7.6 years. The time spent in ST and PA was measured with triaxial accelerometry. Quality of life and disease impact were assessed using the Short Form 36 (SF-36) health survey and the Revised Fibromyalgia Impact Questionnaire (FIQR), respectively. The substitution of ST with an equivalent time of LPA or MVPA and the associated outcomes were examined using isotemporal substitution analyses. Results: Substituting 30 minutes of ST with LPA in the isotemporal model was associated with better scores in bodily pain (B = 0.55), vitality (B = 0.74), and social functioning (B = 1.45) according to the SF-36, and better scores at all of the domains (function, overall impact, symptoms, and total impact) of the FIQR (B ranging from -0.95 to -0.27; all P < 0.05). When ST was replaced with MVPA, better physical role (B = 2.30) and social functioning (B = 4.11) of the SF-36 and function of the FIQR (B = -0.73) were observed (all P < 0.05). Conclusion: In regression models, allocation of time of sedentary behavior to either LPA or MVPA was associated with better quality of life and lower disease impact in women with fibromyalgia
Keywords: Fibromialgia; calidad de vida; actividad física; tiempo sedentario